2005 IEEE Engineering in Medicine and Biology 27th Annual Conference 2005
DOI: 10.1109/iembs.2005.1617234
|View full text |Cite
|
Sign up to set email alerts
|

Measurement System for the Characterization of the Human Body as a Communication Channel at Low Frequency

Abstract: Electronic data transfer by capacitive and galvanic coupling through the human body has been proposed by research and industry as a novel but highly promising technology for ultra low power wireless body LANs. Investigation on the most challenging questions considering data communication becomes enabled with a highly versatile measurement system for frequencies in the range of 10 kHz to 1 MHz. The human body is characterized as a transmission medium for electrical current by means of measurements and is invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…A range of different network and communication protocols have been developed for electronics during the last decades that extend connectivity and distribution of the web throughout our society. Body area networks (BANs), based on traditional Si-chip technology, have been proposed and developed 9,10 and standards are also evolving 11 . These take use of the human body as a communication channel with, for instance, our hands as the galvanic or capacitive connectors.…”
Section: Introductionmentioning
confidence: 99%
“…A range of different network and communication protocols have been developed for electronics during the last decades that extend connectivity and distribution of the web throughout our society. Body area networks (BANs), based on traditional Si-chip technology, have been proposed and developed 9,10 and standards are also evolving 11 . These take use of the human body as a communication channel with, for instance, our hands as the galvanic or capacitive connectors.…”
Section: Introductionmentioning
confidence: 99%
“…The new component electrooptic sensor was introduced in the transceiver by Shinagawa et al [80]; a data rate of 10 Mbps was reached. The comparison of modulation schemes FSK and BPSK was conducted by Wegmueller et al [43]. It was found that, with input current of 2 mA, BPSK and FSK obtained a data rate of 255 kbps and 128 kbps, respectively.…”
Section: Static Body Behaviormentioning
confidence: 99%
“…After the pioneering work of successfully implementing HBC, considerable researches have been conducted by research groups to investigate the channel gain at different distances and regions of body such as arm, thorax, leg, and the back [43,44]. Accompanying with the experimental investigations, the theoretical researches on the transmission mechanism have become a major research topic.…”
Section: Electrical Properties Of Human Tissues and Hbc Signal Propagmentioning
confidence: 99%
“…The basic theory of BCC is that a small electric field is induced into the human body in order to propagate a signal between devices that are in the impedance of [16], or in direct contact with, the human body. The two conceptually different approaches to motivate the electrical signal onto the body have been in advance proposed first capacitive coupling and second galvanic coupling.…”
Section: The Body Couple Communication (Bcc) Technologymentioning
confidence: 99%